2017
DOI: 10.1111/bjh.14545
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of whole-body ultra-low dose computed tomography in comparison with spinal magnetic resonance imaging in the assessment of disease in multiple myeloma

Abstract: This study compared the diagnostic value of Whole-Body Ultra Low-Dose computed tomography (WBULDCT) with that of Spinal Magnetic Resonance Imaging (SMRI) in identification of spinal bone marrow involvement in patients with Multiple Myeloma (MM). Thirty-five patients with histologically proven MM underwent WBULDCT and dedicated SMRI. Unenhanced WBULDCT was performed on a 256-slice scanner, with 120 kV and 40 mAs. SMRI was performed on a 1·5T magnet, with T1-turbo spin echo and T2-short tau inversion recovery se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The widespread availability of multi-detector CT scanners has contributed to the increased use of WBLDCT for the diagnosis and follow-up of MM. The total effective dose of the WBLDCT in our study is comparable to those reported in recent literature [24][25][26][27]. Moreover, our measured organ specific dose is comparable to the organ dose described by Kröpil DLP dose length product, CTDI vol volume computed tomography dose index, NA not applicable/available et al [28].…”
Section: Discussionsupporting
confidence: 88%
“…The widespread availability of multi-detector CT scanners has contributed to the increased use of WBLDCT for the diagnosis and follow-up of MM. The total effective dose of the WBLDCT in our study is comparable to those reported in recent literature [24][25][26][27]. Moreover, our measured organ specific dose is comparable to the organ dose described by Kröpil DLP dose length product, CTDI vol volume computed tomography dose index, NA not applicable/available et al [28].…”
Section: Discussionsupporting
confidence: 88%
“…The concordance in spinal distribution of lesions was 61Á6% on cervical, 71Á5% on dorsal, 86Á4% on lumbar and 94Á4% on sacral, while for the pattern of disease, it was 56Á1% for the focal and 88Á7% for the combined pattern. Cohen's kappa index was 0Á85 (P < 0Á001), assessing an excellent agreement (Ippolito et al, 2017). I should like to raise 3-4 methodological and statistical points regarding diagnostic value.…”
mentioning
confidence: 90%
“…One more important thing is our approach to assess validity is global average; however, an individual based approach should be considered to correctly assess reliability. Ippolito et al (2017) concluded that WBULDCT represents a useful diagnostic tool in the detection of spinal involvement of MM patients, offering detailed information about extra-axial involvement, which could be potentially missed with dedicated SMRI. Here, I have discussed the limitations of their approach and the lack of evidence for such a …”
mentioning
confidence: 99%
See 2 more Smart Citations